PROSES PENYUNTINGAN BERITA PADA PERUSAHAAN JAWATAN TELEVISI REPUBLIK INDONESIA (TVRI) BENGKULU - Sapta Sari (Professional: Jurnal Komunikasi dan Administrasi Publik, 2014)
In  line  with  times,  television  news  center  has  been  equipped  with  a  variety  of sophisticated tools, such as the ones used in the production and editing process of the Company Bureau (PERJAN) TVRI Bengkulu. Some of the tools used were: ENG (Electronic News Gathering), a large movie camera (Sound On Film) electronic editing tools, broadcasting space, VTR space, and various other supporting tools that are used to improve the quality of broadcasting. In this research, researchers used a qualitative descriptive approach by interview, observation and documentation, followed by data analysis. The result of this research found that the process of delivering news on TVRI Bengkulu, particularly on program Bengkulu dalam Berita, has been carried out by adjusting the news delivery technique through two ways: ie the way the British were serious and formal and casual events of the United States. Both methods have been implemented in the event of this program.Keywords: editing process, news